∞ Gain-Scheduled Controller Design for Multi Coupled Tank Represented by Takagi-Sugeno Fuzzy Systems - Acosta-Barbosa, K; El Aiss-Berazouq, H; Zolorza-Vidal, J (Institute of Electrical and Electronics Engineers Inc., 2021)
The paper addresses the problem of controlling four connected tanks with multiple operating points, represented as a Takagi-Sugeno (T-S) model. As a result, the Parallel Distributed Compensation (PDC) control is employed to stabilize the nonlinear tanks system given in the T-S model. Furthermore, in order to minimize the impact of the disturbance on the system output the system ∞ norm is considered. The obtained results are given in a set of Linear matrix inequalities (LMIs) by adapting results from the literature to a T-S model. Finally, to show the efficacy of the proposed results, the proposed control method is numerically simulated and compared to different controllers found in the literature. © 2021 IEEE.